Effects of acute and chronic exercise on working memory in healthy adults. An experimental investigation - Borrega-Alonso, Eva; Otamendi, F. Javier (Frontiers in Psychology, 2025)
IntroductionWorking memory is critical for optimal development of academic and occupational functions, and its deterioration is associated with mental health issues. Exercise-based interventions have emerged as a prominent strategy to enhance cognitive functions and improve mental health. The objective of this study is to analyze the effects of both acute and chronic physical exercise on working memory in the context of cognitive and experimental psychology.MethodsParticipants (73 adults aged between 18 and 65 years) performed appraisal tests on working memory based on image recovery (Test 1) and decision-making on verbal mathematical operations (Test 2), with the experimental group performing one-hour intense functional training (acute exercise) immediately before. The World Health Organization (WHO) classification based on weekly chronic exercise was also used for categorization of participants.ResultsThe results show that both types of physical activity positively affect cognition. Chronic exercise favored all aspects of working memory (verbal mathematical operations and decision making; p-value = 0.014; pη2 = 0.081//image recovery; p-value = 0.033; pη2 = 0.062), while acute exercise only favored those related to image recovery (p-value = 0.007; pη2 = 0.099).ConclusionTo enhance working memory, it is recommended that both companies and educational centers promote both types of physical exercise. For future research, in addition to increasing the sample size, it would be beneficial to vary the length of training as well as the difficulty of the assessment tests.